PH Driven Encapsulation Of Curcumin In Self-Assembled Niosome Curcuminoid Physical Characterizations, Encapsulation Efficiency & Stability Study - Kalidas, Saravanan Reddy (Universiti Sains Malaysia, 2018)
Curcumin is an antioxidant with various healing properties but possesses limitation due to its poor solubility and reduced bioavailability as pH influences greatly on curcumin. Niosomes are composed of non-ionic surfactants and act as transport vesicle for drug delivery to overcome the limitations of curcumin as a potential drug. The aim of this study was to investigate the influence of different pH on the physiochemical properties of curcumin-loaded niosomes. The niosomes were composed of 1:1 mole ratio of Span 60: Tween 60 as vesicle-forming agents and prepared using thin film hydration method. The influence of formulation on vesicle size, entrapment efficiency (EE) and stability of curcumin-loaded niosomes was investigated. Transmission electron microscopy (TEM) revealed that niosomes at pH 3 and 7 had a spherical shape and uniform distribution, while pH 9 produced irregularly shaped niosomes. The results showed that the incorporation of curcumin into niosome at pH 3 yielded vesicles with larger sizes (394.07 ± 17.35 nm to 556.37 ± 28.44 nm) compared to other pH formulation before extrusion. However, after extrusion the size has been significantly reduced to smaller sizes (150.30 ± 2.29 nm to 156.30 ± 2.17 nm). Furthermore, the EE of curcumin niosomes at pH 3 was highest (75.23%) than that of niosomes at pH 7 and 9. The zeta potential at pH 3 was also remarkably lower than pH 7 and 9, yet decreases gradually over time. After 28 days storage, it was found that freezer storage (-4'C) had the highest stability with less reduction in EE. The size of all the formulation increased and started to aggregate when the temperature and storage period increases indicating lower stability at a higher temperature.